Klimatreducerande lösningar för en prefabricerad betongstomme - Hansson,William; Nilsson,Sebastian (0349-4969, 2025)
The construction industry is responsible for approximately 20% of Sweden’s annual greenhouse gas emissions and plays a key role in achieving national climate goals. As building operations become more energy efficient, emissions from the construction phase, particularly from concrete frameworks become increasingly significant. This thesis investigates emission reducing alternatives for a fully prefabricated concrete framework through a case study of the Godsfinkan 3 project. Climate calculations show that the fully prefabricated frame has 20,3% higher emissions than a partially prefabricated one but still meets Sweden’s 2025 carbon limit. To achieve future climate goals, improvements to the prefabricated concreate element of the structural framework are primarily required. By solely improving the climate performance of the concreate elements, emissions are reduced by 13,7% to 20,2%, with associated costs of up to 3,4%. Implementing a combination of climate improved concreate elements and reduced transport distances resulted in an emission reduction of 29,4%. This thesis highlights the potential for combining multiple low-carbon strategies to significantly reduce the climate impact of concrete buildings.
Keywords: Klimatdeklaration; klimatberäkning; Prefabricerad betongstomme; Klimatförbättrad byggnation